Supersensitivity Psychosis and Its Response to Asenapine in a Patient with Delusional Disorder - Ravi Philip Rajkumar (Case Reports in Psychiatry)
Supersensitivity psychosis is a recognized complication of long-term antipsychotic treatment, in which patients develop new or reemergent psychotic symptoms, generally accompanied by dyskinetic movements, due to prolonged dopamine receptor blockade and resultant supersensitivity. Though it is most closely associated with schizophrenia and the use of typical antipsychotic agents, it has also been documented in patients with other diagnoses, and in those receiving atypical antipsychotics. There is no established treatment for this condition. In this paper, we describe a patient with persistent delusional disorder, jealous type, who developed a supersensitivity psychosis characterized by persecutory delusions, auditory hallucinations, and thought insertion in association with mild tardive dyskinesia. These symptoms resolved completely following six weeks of treatment with the second-generation antipsychotic asenapine, 20 mg/day. The mechanisms and implications of the patient’s symptomatology and response are discussed.